PERAN GURU DALAM INTERAKSI SOSIAL SISWA BERKEBUTUHAN KHUSUS TUNAGRAHITA - Dian Ayu Qori’atul Karisma; Louis Bernica Quinnunez; Sulistiya Mitakhuzahro; Rita Intan Marlina; Finani Fatimatus Zahro; Galih Setiawati; Faruq Faruq (Guidance and counseling the university of Prof. Dr. Hazairin. SH, 2025)
Social interaction is a relationship between other individuals that influence each other and create a reciprocal relationship. Some parents who are gifted with mentally disabled children think that their children experience difficulties in social interaction, so the role of the teacher is very much needed in teaching how to interact socially with their abilities. The research aims to determine the roles, methods, and factors that influence teachers' social interactions with children with special needs with mental retardation. Qualitative methods are used in this research. Phenomenological approach as a qualitative design. A purposive sampling technique was applied when determining the subject. Data were collected by interviewing for about 60-90 minutes, consisting of 14 questions and 6 participants. The study results show that the teacher's role is needed to form social interactions. The teacher acts as a provider of direction and support, methods such as outing classes and parenting factors also affect teachers' social interactions with mentally disabled children.